Asbestos Bodies Burden in the Autopsy Lung Tissue from General Thai Population - Incharoen, Pimpin (Open Respir Med J, 2019)
BACKGROUND: Chrysotile asbestos has been used in Thailand for over 30 years mainly in asbestos-cement wall and roof tiles. In non-exposed subject, asbestos fiber can contaminate in ambient indoor and outdoor environments. OBJECTIVE: The aim of the present study is to evaluate the current prevalence and volume of AB load in general Thai population. METHODS: Lung tissues were obtained from 200 autopsy cases. Asbestos Bodies (AB) were identified with light microscopy using the tissue digestion and membrane filtration method. Results are reported as AB/g wet lung tissue. RESULTS: AB was identified in 97(48.5%) out of 200 cases. The AB level ranged from 0.19-14.4 AB/g wet lung. Most of the positive cases (99%) have less than 10 AB/g wet lung. Only one case exhibited a high value at 14.4 AB/g wet lung. Age, gender, occupation and hometown were found to have no effect on AB burden in autopsy lung tissue from this study. CONCLUSION: The prevalence of AB in autopsy lung tissue from general Thai population is 48.5% and the AB level ranges from 0-14.4 AB/g wet lung in consistent with non-occupational asbestos exposure level regarding several reference reports.